Modeling and real-time simulation of internal faults in turbogenerators - Sinha A.; Vishwakarma D.N.; Srivastava R.K. (My University, 2025)
When an internal fault occurs in the lap-connected windings of turbogenerators, the symmetry between the parallel windings is broken, and different currents then flow because unsymmetrical magnetic linkage exists between the stator windings. The aim of this article is to present a real-time simulation model to investigate the internal fault currents in large turbogenerators with lap windings. This model is based on a modified winding function approach, where the machine inductances are calculated directly from the machine winding distribution. The calculation of the machine inductances are made easier by the use of machine electrical parameters instead of geometrical parameters. The simulation results have been obtained for different cases of internal faults. By using simulated internal fault data, a suitable numerical protection scheme for turbogenerators can be developed.